2021
DOI: 10.2196/24687
|View full text |Cite
|
Sign up to set email alerts
|

Improving Management of Type 2 Diabetes Using Home-Based Telemonitoring: Cohort Study

Abstract: Background Diabetes is present in 10.5% of the US population and accounts for 14.3% of all office-based physician visits made by adults. Despite this established office-based approach, the disease and its adverse outcomes including glycemic control and clinical events tend to worsen over time. Available home technology now provides accurate, reliable data that can be transmitted directly to the electronic medical record. Objective This study aims to eva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…A large number of studies have reported the necessity and utility of telehealth through various applications for patients with DM2, including telelearning, telemonitoring, DM self-management, and telecounseling [ 21 , 24 , 41 , 42 ]. Telemedicine studies, such as the research by Milani [ 23 ], have shown that telehealth applications can increase glycemic control, reduce glycated hemoglobin values, and improve the quality of life [ 43 , 44 , 45 ]. Regarding the implementation of telerehabilitation for diabetic patients, only one study by Duruturk (2019) has investigated the effect of a remote intervention in glucose control, physical activity, muscle strength, and patient’s psychosocial status [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have reported the necessity and utility of telehealth through various applications for patients with DM2, including telelearning, telemonitoring, DM self-management, and telecounseling [ 21 , 24 , 41 , 42 ]. Telemedicine studies, such as the research by Milani [ 23 ], have shown that telehealth applications can increase glycemic control, reduce glycated hemoglobin values, and improve the quality of life [ 43 , 44 , 45 ]. Regarding the implementation of telerehabilitation for diabetic patients, only one study by Duruturk (2019) has investigated the effect of a remote intervention in glucose control, physical activity, muscle strength, and patient’s psychosocial status [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Home-based telemonitoring has proven to be a safe and effective alternative to center-based programs and can result in higher exercise compliance [ 20 ] and compliance with dietary recommendations in patients with DM2 [ 21 ]. Thus, telehealth could represent a valuable method to improve blood sugar control, prevent rehospitalization, enhance the quality of life, and improve adherence rates to therapeutic interventions in patients with DM2 [ 21 , 22 , 23 ]. Telehealth services also reduce costs and increase the potential to attend more sessions compared to center-based facilities [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, portable electrochemical glucose meters have improved the quality of life of many people who have diabetes [173]. It has been demonstrated that regular remote reporting of results using SbSs can improve patients' outcomes [174].…”
Section: Potential Social Impact In Diagnostics For Elderly Individualsmentioning
confidence: 99%
“…This pilot study demonstrates the feasibility of remote glucose monitoring among pediatric patients with newly diagnosed T1D using Bluetooth-capable glucose meters and Wi-Fi-enabled mobile devices. Remote glucose monitoring has been utilized previously for adults with type 2 diabetes [9,10], and for children with T1D utilizing insulin pumps [11] or CGM devices [12].…”
Section: Primary Findingsmentioning
confidence: 99%